Niger germplasm evaluation for major morphological and agronomical traits: Niger germplasm evaluation for major morphological and agronomical traits - H D PUSHPA; M SUJATHA; D P MEGHANA; HELAN BABY THOMAS; PRADUMAN YADAV; CH KRISHNA CHAITANYA; H BASAMMA; PRASHANT K JAGTAP; RAJANI BISEN; S RAJKUMAR (Journal of Oilseeds Research, 2023)
A panel of niger (Guizotia abyssinica (L.f) Cass) accessions were augmented and evaluated to characterize for various morphological and agronomical traits. The analysis of variance has shown that there was a significant variation observed among the genotypes. Variability analysis revealed that the oil content had high GCV with high broad sense heritability. High PCV was observed among the other yield related traits which indicates that these traits are highly influenced by the environmental factors.